Flash-PEO as an alternative to chromate conversion coatings for corrosion protection of Mg alloy. (March 2021) - Wierzbicka, E.; Vaghefinazari, B.; Lamaka, S.V.; Zheludkevich, M.L.; Mohedano, M.; Moreno, L.; Visser, P.; Rodriguez, A.; Velasco, J.; Arrabal, R.; Matykina, E.
Highlights: Flash PEO ensures low energy consumption of the coating synthesis. 4-Methylsalycilate-loaded PEO coating ensures active corrosion protection of Mg. Inhibitor-loaded PEO coatings are more protective than chromate conversion coatings. Excellent full system performance in paint adhesion and neutral salt spray tests. Flash-PEO/inhibitor/Li-leaching primer system outperforms CCC/chromated primer. Abstract: In the present work, a flash-PEO coating is developed on AZ31B alloy in a combination of silicate, phosphate, and fluoride based electrolyte in order to offer a green alternative to chromate conversion coatings. Multilevel active protection is achieved through synergetic combination of self-sealing effect of PEO coating itself and active inhibition provided by an organic inhibitor impregnated in PEO pores in a post-treatment step. The results indicate that flash-PEO coatings, loaded with organic corrosion inhibitors, can be recommended for exploitation on industrial level as an equally effective corrosion protection system alternative to CCC for paint-bearing and paint-free applications.